Acceptance of Diversity as a Building Block of Social Cohesion: Individual and Structural Determinants - Arant, Regina; Larsen, Mandi; Boehnke, Klaus (Frontiers in Psychology, 2021)
High levels of social cohesion have been shown to be beneficial both for social entities and for their residents. It is therefore not surprising that scholars from several disciplines investigate which factors contribute to or hamper social cohesion at various societal levels. In recent years, the question of how individuals deal with the increasing diversity of their neighborhoods and society as a whole has become of particular interest when examining cohesion. The present study takes this a step further by combining sociological and psychological approaches in investigating whether the group-level acceptance of diversity, a core feature of cohesive societies, is related to prevailing mentalities of individuals once the social structure of a community is accounted for. We hypothesize that after controlling for individual sociodemographic and structural variables, three individual characteristics play an important role for the level of acceptance of diversity in a given entity. We propose that individual intergroup anxiety acts as a motor of the rejection of diversity whereas individual empathy should act as a safeguard. Furthermore, we propose that right-leaning political orientation has a negative influence on the acceptance of diversity. This study is based on a large, representative sample of the German general population (N1 = 2,869). To draw comparisons among different social entities, the sample was divided by federal states (N2 = 16). Data were analyzed by using a two-step approach for analyzing group-level outcomes in multilevel models. The analyses confirmed our hypothesis that intergroup anxiety at the individual level hampers the acceptance of diversity in a given sociopolitical entity. Furthermore, we found that intergroup anxiety is impacted by the economic situation in a federal state (measured as GDP per resident), as economic weakness intensified the fear of others. Surprisingly, neither empathy or political orientation played a role for the acceptance of diversity. Implications for future research on social cohesion as well as for the work of policy makers are discussed.